Shortening self‐report mental health symptom measures through optimal test assembly methods: Development and validation of the Patient Health Questionnaire‐Depression‐4. Issue 1 (20th September 2018) - Ishihara, Miyabi; Harel, Daphna; Levis, Brooke; Levis, Alexander W.; Riehm, Kira E.; Saadat, Nazanin; Azar, Marleine; Rice, Danielle B.; Sanchez, Tatiana A.; Chiovitti, Matthew J.; Cuijpers, Pim; Gilbody, Simon; et al.
Abstract : Background: The objective of this study was to develop and validate a short form of the Patient Health Questionnaire‐9 (PHQ‐9), a self‐report questionnaire for assessing depressive symptomatology, using objective criteria. Methods: Responses on the PHQ‐9 were obtained from 7, 850 English‐speaking participants enrolled in 20 primary diagnostic test accuracy studies. PHQ unidimensionality was verified using confirmatory factor analysis, and an item response theory model was fit. Optimal test assembly (OTA) methods identified a maximally precise short form for each possible length between one and eight items, including and excluding the ninth item. The final short form was selected based on prespecified validity, reliability, and diagnostic accuracy criteria. Results: A four‐item short form of the PHQ (PHQ‐Dep‐4) was selected. The PHQ‐Dep‐4 had a Cronbach's alpha of 0.805. Sensitivity and specificity of the PHQ‐Dep‐4 were 0.788 and 0.837, respectively, and were statistically equivalent to the PHQ‐9 (sensitivity = 0.761, specificity = 0.866). The correlation of total scores with the full PHQ‐9 was high ( r = 0.919). Conclusion: The PHQ‐Dep‐4 is a valid short form with minimal loss of information of scores when compared to the full‐length PHQ‐9. Although OTA methods have been used to shorten patient‐reported outcome measures based on objective, prespecified criteria, further studies are required to validate this general procedure for broader use in health research. Furthermore, due to unexamined heterogeneity, there is a need to replicate the results of this study in different patient populations.